2018
DOI: 10.1002/ps.5142
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds produced by castor bean cake incorporated into the soil exhibit toxic activity against Meloidogyne incognita

Abstract: Castor bean cake incorporated into the soil produces volatile compounds which are toxic to M. incognita. These substances show potential for application in the nematicide-producing industry. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 26 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…They also showed in a sterile system that the microbes attaching to the cuticle of M. hapla in the suppressive soil induced systemic resistance in the plant upon nematode invasion (Topalović et al, 2020a). In addition, in recent years scientists have intensively explored the role of plant and microbial volatile organic compounds on nematode parasitism (Huang et al, 2010;Yang et al, 2012;Barros et al, 2014;Xu et al, 2015;Estupiñan-López et al, 2018;Silva et al, 2018;Pedroso et al, 2019). Thus, the potential of root microbiota to assist plants in fighting PPN is enormous.…”
Section: Importance Of the Rhizosphere Microbiota In Plant-nematode Imentioning
confidence: 99%
“…They also showed in a sterile system that the microbes attaching to the cuticle of M. hapla in the suppressive soil induced systemic resistance in the plant upon nematode invasion (Topalović et al, 2020a). In addition, in recent years scientists have intensively explored the role of plant and microbial volatile organic compounds on nematode parasitism (Huang et al, 2010;Yang et al, 2012;Barros et al, 2014;Xu et al, 2015;Estupiñan-López et al, 2018;Silva et al, 2018;Pedroso et al, 2019). Thus, the potential of root microbiota to assist plants in fighting PPN is enormous.…”
Section: Importance Of the Rhizosphere Microbiota In Plant-nematode Imentioning
confidence: 99%
“…exposure of M. incognita second‐stage juveniles (J 2 ) to 3‐methylbutyl acetate at 500 μg mL 1 for 1 h caused mortality above 84% . In recent years, studies on the use of plant VOCs against PPNs have expanded . Biofumigation, consisting of the incorporation of plant residues that slowly release their bioactive compounds into the soil, has been successfully used to control PPNs since the 19th century .…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, studies addressing VOCs released by plant residues have revealed a number of molecules with nematicidal activity similar to commercial nematicides, therefore further studies are needed to identify VOCs emitted in biofumigation processes. Volatiles toxic to PPNs can be determined when VOCs are identified from plant emissions and individually tested against specific PPNs, enabling the discovery of new nematicidal compounds with high environmental and health safety …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations